Analysis of Uniform Distribution of Storage Nodes in Wireless Sensor Network - Kukade, Madhavi S; Hande, Kapil N (International Journal of Computer Sciences and Engineering, 2014)
Sensors networks are capable of collecting an enormous amount of data over space and time .Often ,the ultimate objective is to “sample, store and forward ” that is to sense the data , store it locally and ultimately forward it to accent almost and analyzed. Typical sensor nodes are wireless nodes with limited storage and computational power . Furthermore they are prone to “failure” by going out of wireless range, interference running out of battery etc. The sensor and storage nodes are distributed randomly in some region and can not maintain routing tables or shared knowledge of network topology .Some nodes might disappear from the network due to failure or battery depletion overall this problem has occurred for overcoming this problem so many techniques are studied in this paper.